(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Heterocyclic compounds have a role in most fields of sciences such as medicinal chemistry, biochemistry also another area of sciences. More than 90 of new drugs contain heterocycles and the interface between chemistry and biology, at which so much new scientific insight, discovery and application is taking place is crossed by heterocyclic compounds. Compounds derived from heterocyclic rings in pharmacy, medicine, agriculture, plastic, polymer and other fields. Most active heterocycles have shown considerable biological actions as antifungal, anti-inflammatory, antibacterial, anticonvulsant, antiallergic, herbicidal, anticancer activity. In this study, we will understand the biologically active heterocyclic compound, its classification, biological importance of nitrogen-containing heterocyclic compound.